Epileptic seizure prediction using bandpass filtering and convolutional neural network - Rahman, Tasnia; Mustaqeem, Nabiha; Priyo, Jannatul Ferdous Binta Kalam; Shahariar, Ahnaf; Sharmin, Shaila (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.